Healthy Living Education for Preventing Childhood Infectious Diseases: A Literature Review - Phalis, Annisa Putri Ana; Yasin, Agustina M.; Sukmawati, Sukmawati; Sudirman, Sudirman; Yani, Ahmad; Amalinda, Finta (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
The increasing incidence of infectious diseases among children highlights the urgent necessity for effective health education programs emphasizing clean and healthy behaviors. This study aims to identify the determinants influencing the effectiveness of health education in preventing infectious diseases in children. A systematic literature review was performed, analyzing 15 peer-reviewed articles retrieved from databases including PubMed, Scopus, and Web of Science, encompassing publications from 2019 to 2024. The search strategy employed keywords such as